2023
DOI: 10.25100/socolen.v49i2.12526
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuación poblacional de Scolytinae (Coleoptera: Curculionidae) en huertos de aguacate (Persea americana Mill.) en Michoacán, México

Martha Olivia Lázaro-Dzul,
Armando Equihua-Martínez,
Jesús Romero-Nápoles
et al.

Abstract: El objetivo de este estudio fue determinar la fluctuación poblacional de Scolytinae (Coleoptera: Curculionidae) en huertos de aguacate (Persea americana var. Hass), ubicados en los municipios de Nuevo San Juan Parangaricutiro (SJ), Uruapan (UR), y Ziracuaretiro (ZR), Michoacán, México, durante julio de 2016 a junio de 2018. Los insectos se recolectaron con trampas tipo botella, cebadas con compuestos atrayentes alfa-copaeno, etanol y la combinación querciverol + etanol. La fluctuación poblacional de Scolytinae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Querciverol was less attractive, with a mean of 0.92. Lázaro (2019) previously reported lack of effectiveness of attractant in a study in 'Hass' avocado orchards at Michoacán. However, Wood (1982), Rabaglia (2009), andRanger et al (2010) reported the best attractant for Scolytines was ethanol recommended especially for traps.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Querciverol was less attractive, with a mean of 0.92. Lázaro (2019) previously reported lack of effectiveness of attractant in a study in 'Hass' avocado orchards at Michoacán. However, Wood (1982), Rabaglia (2009), andRanger et al (2010) reported the best attractant for Scolytines was ethanol recommended especially for traps.…”
Section: Resultsmentioning
confidence: 96%
“…Combinations of attractants can have a synergic effect, as mentioned by Kendra et al (2017) and Owens et al (2019), because combining attractants alpha-copaene and querciverol increased the number of E. kuroshio captured and lengthened the useful period of the attractants in the field. Both attractants were used singly (Lázaro et al 2019, Velázquez 2020) and combined (García et al 2018) to monitor native beetles in avocado and fig orchards.…”
Section: Introductionmentioning
confidence: 99%
“…Las especies encontradas en orden de abundancia fueron Premnobius cavipennis (n=774), Xyleborus volvulus (n=126), Xyleborus affnis (n=33) y Xyleborus palatus (n=32), Corthylus sp (n=1) y Hypothenemus sp (n=1). Premnobius cavipennis figura como la quinta especie de escarabajo escolitino mayormente encontrada en huertos de aguacate en el estado de Michoacán (Lázaro-Dzul et al, 2023); mientras que X. volvulus, X. affinis y X. palatus fueron encontrados en huertos de Michoacán, Estado de México y Nayarit, respectivamente (Laureano- Ahuelicán et al, 2022;Jacobo-Macias et al, 2021). Conclusión.…”
unclassified